Study of Judge's Decisions in Upholding Restorative Justice Law for Defendants and Victims of Underage Children - Nurul Fatimah Az Zahro; Muchamad Iksan; Natangsa Surbakti; Peggy Dian Septi Nur Angraini (LEGAL BRIEF, 2022)
The criminal act of intercourse committed by the accused and the victim under the age of the need to apply restorative justice where the child is a form of hope to continue the hopes of the nation and state. This research method is normative juridical with statutory and case approaches and comparisons. The aim of the research is to find out and analyze the law enforcement of restorative justice for defendants under the age of study, Decision Number: 1/Pid.Sus-Anak/2021/Pn, Decision Number: 7/Pid.Sus-Anak/2021/Pn.Skt , and Decision Number 9/Pid.Sus-Children/2021/Pn.Skh. The results of the research show that Decision Number: 1/Pid.Sus-Anak/2021/Pn and Decision Number: 7/Pid.Sus-Anak/2021/Pn.Skt do not apply restorative justice where the judge prefers to impose prison sentences on children. Meanwhile, Decision Number 9/Pid.Sus-Anak/2021/Pn.Skh. has implemented restorative justice in the form of more action being imposed than to carry out imprisonment for children. Indeed, the crime of intercourse is not included as a crime that is resolved by restorative justice, but it needs to be seen as more in order to give the child offender the opportunity to understand the consequences of his actions and take responsibility and the community can understand the causes of crime for the sake of welfare and crime prevention. Keywords: Law Enforcement; Restorative Justice; Minors; Tindak pidana persetubuhan yang dilakukan oleh terdakwa dan korban di dibawah umur perlu menerapkan keadilan restoratif dimana anak adalah wujud harapan penerus harapan cita-cita bangsa dan negara. Metode penelitian ini adalah yuridis normatif dengan pendekatan perundang-undangan dan kasus serta perbandingan. Tujuan penelitian adalah untuk mengetahui dan menganalisis penegakan hukum keadilan restoratif justice terhadap terdakwa anak di bawah umur studi Putusan Nomor : 1/Pid.Sus-Anak/2021/Pn, Putusan Nomor : 7/Pid.Sus-Anak/2021/Pn.Skt, dan Putusan Nomor 9/Pid.Sus-Anak/2021/Pn.Skh. Hasil penelitian menunjukkan bahwa Putusan Nomor : 1/Pid.Sus-Anak/2021/Pn dan Putusan Nomor : 7/Pid.Sus-Anak/2021/Pn.Skt tidak menerapkan keadilan restoratif dimana hakim lebih memberikan penjatuhan hukuman pidana penjara terhadap anak. Sedangkan Putusan Nomor 9/Pid.Sus-Anak/2021/Pn.Skh. telah menerapkan keadilan restoratif berupa lebih dijatuhkan tindakan dibandingkan untuk melakukan penghukuman pidana penjara terhadap anak. Memang dalam tindak pidana persetubuhan tidak termasuk tindak pidana yang diselesaikan dengan keadilan restoratif tapi perlu dipandang lebih guna memberi kesempatan pelaku anak untuk memahami akibat tindakan dan bertanggungjawab serta masyarakat dapat memahami sebab kejahatan demi kesejahteraan dan pencegahan kejahatan. Kata kunci : Penegakan Hukum; Restoratif Justice; Anak dibawah umur;